Impact of surgeon volume on 18‐month unclosed ileostomy rate after restorative rectal cancer resection. (29th October 2022) - Tyler, Robert; Foss, Helen; Phelan, Liam; Radley, Simon; Geh, Ian; Karandikar, Sharad
Abstract: Aim: The impact of surgeon volume on 18‐month unclosed ileostomy rates after rectal cancer surgery has not been fully explored. The aim of this study was to describe the effect of surgeon volume and evaluate factors predictive of an unclosed ileostomy. Method: Patients undergoing anterior resection with a diverting ileostomy for rectal cancer from March 2004 to October 2018 were identified from a prospectively maintained database. The unclosed ileostomy rate was determined by those with an unclosed ileostomy at 18 months. High‐ and low‐volume surgeons (HVS and LVS, respectively) were classed as those performing five or more or fewer than five rectal cancer resections per year, respectively. Data on sex, age, American Society of Anesthesiologists grade, neoadjuvant chemoradiotherapy (CRT), tumour height, T‐stage, anastomotic leak, surgical approach and adjuvant chemotherapy were also collected. Factors predictive of an unclosed ileostomy at 18 months were explored using a multivariate binary logistic regression analysis. Results: A total of 415 patients (62.4% male) with a median age of 67 were eligible for analysis. Of these, 115 (27.7%) had an unclosed ileostomy at 18 months. HVS had an unclosed ileostomy rate of 24.6% (72/292) compared with 34.9% (43/123) for LVS. Volume was associated with an unclosed ileostomy in univariable analysis ( p = 0.032) but not in multivariate analysis (OR 1.75, 95% CI 0.92–3.32, p = 0.08). Independent factors predictive of an unclosed ileostomy were anastomotic leak (OR 10.41, 3.95–27.0, p < 0.01), adjuvant chemotherapy (OR 2.23, 1.24–3.96, p < 0.01) and neoadjuvant CRT (OR 2.16, 1.15–5.75, p = 0.01). Conclusion: LVS were associated with a higher unclosed ileostomy at 18 months compared with HVS. This study adds further weight to the call for adoption of a minimum annual case threshold in rectal cancer surgery.